Sex Determination of Superorder Neognathae (class Aves) by Molecular Genetics Methods - Michal Gábor; Martina Miluchová; Anna Trakovická; Cyril Hrnčár; Eva Radosová (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was optimization molecular genetic method for sex determination of superorder Neognathae from class Aves. The basis of the molecular-genetic methods was the amplification of a chromo-helicase DNA binding 1 (CHD) gene region, which is located in both sex chromozomes Z and W. Genomic DNA was isolated from whole blood and feathers by using commercial column kit QIAamp DNA Mini kit. The intron regions of CHDW and CHDZ genes were amplified by sex specific primers P2 and P8. The PCR method used in this study was based on two differences between CHDW and CHDZ genes. The one of these differences is restriction site for endonuclease HaeIII located only in CHDZ and the second is the lenght polymorphism between CHDW and CHDZ where for the males was detected one band and for the females were detected two bands in 3.5 % agarose gel. These molecular-genetics methods were successfully used for sex determination in 36 species from superorder Neognathae.